Fluid shear stress promotes osteoblast proliferation via the Gαq–ERK5 signaling pathway. (3rd July 2016) - Bo, Zhang; Bin, Geng; Jing, Wang; Cuifang, Wang; Liping, An; Jinglin, Ma; Jin, Jiang; Xiaoyi, Tan; Cong, Chen; Ning, Ding; Yayi, Xia
ABSTRACT: Fluid shear stress (FSS) is a ubiquitous mechanical stimulus that potently promotes osteoblast proliferation. Previously, we reported that extracellular signal–regulated kinase 5 (ERK5) is essential for FSS-induced osteoblast proliferation. However, the precise mechanism by which FSS promotes osteoblast proliferation via ERK5 activation is poorly understood. The aim of this study was to determine the critical role of Gαq in FSS-induced ERK5 phosphorylation and osteoblast proliferation, as well as the downstream targets of the Gαq–ERK5 pathway. MC3T3-E1 cells were transfected with 50 nM Gαq siRNA, treated with 5 mM XMD8-92 (a highly selective inhibitor of ERK5 activity), and/or exposed to FSS (12 dyn/cm 2 ). Cell proliferation was evaluated using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The protein expression levels of Gαq, P-ERK5, ERK5, Cyclin B1, and CDK1 were analyzed by Western blot. Physiological FSS exposure for 60 min remarkably promoted MC3T3-E1 cell proliferation, however, this effect was suppressed by siRNA-mediated Gαq knockdown or inhibition of ERK5 activity by XMD8-92 treatment, suggesting that Gαq and ERK5 might modulate FSS-increased osteoblast proliferation. Furthermore, ERK5 phosphorylation was dramatically inhibited by Gαq siRNA. In addition, our study further revealed that FSS treatment of MC3T3-E1 cells for 60 min markedly upregulated the protein expression levels of Cyclin B1 and CDK1, and this increased expression was predominantly blocked by Gαq siRNA or XMD8-92 treatment. We propose that FSS acts on the Gαq–ERK5 signaling pathway to upregulate Cyclin B1 and CDK1 expression, thereby resulting in MC3T3-E1 cell proliferation. Thus, the Gαq–ERK5 signaling pathway may provide useful information regarding the treatment of bone metabolic disease.